Desain dan Fabrikasi Printed Circuit Board (PCB) Smartband untuk Mengukur Tanda Vital Pada Tubuh Manusia - Diono, Muhammad; Sasmita Darwis, Rizadi; Al Fitri, Rahmat (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2024)
This research addresses the design and fabrication of a Printed Circuit Board (PCB) for a smartband used to measure vital signs on the human body, including heart rate and body temperature. The main objective of this research is to produce a reliable and accurate device in daily health monitoring. The research process includes system design, design validation, PCB fabrication, component assembly, and testing and calibration. Key components, including heart rate and temperature sensors, were selected and integrated using PCB design software. PCB fabrication was performed through photolithography, etching, drilling, and plating processes. The test results show that the designed PCB meets the expected technical specifications.